Discovery of an Antibiotic-Related Small Protein of Biocontrol Strain Pseudomonas sp. Os17 by a Genome-Mining Strategy - Takeuchi, Kasumi; Tsuchiya, Wataru; Fujimoto, Zui; Yamada, Kosumi; Someya, Nobutaka; Yamazaki, Toshimasa (Frontiers in Microbiology, 2020)
Many root-colonizing Pseudomonas spp. exhibiting biocontrol activities produce a wide range of secondary metabolites that exert antibiotic effects against other microbes, nematodes, and insects in the rhizosphere. The expression of these secondary metabolites depends on the Gac/Rsm signal transduction pathway. Based on the findings of a previous genomic study on newly isolated biocontrol pseudomonad strains, we herein investigated the novel gene cluster OS3, which consists of four genes (Os1348-Os1351) that are located upstream of putative efflux transporter genes (Os1352-Os1355). Os1348 was predicted to encode an 85-aa small precursor protein, the expression of which was under the control of GacA, and an X-ray structural analysis suggested that the Os1348 protein formed a dimer. The mutational loss of the Os1348 gene decreased the antibiotic activity of Pseudomonas sp. Os17 without changing its growth rate. The Os1349-1351 genes were predicted to be involved in post-translational modifications. The status of Os1348 protein detection in cells of the deficient mutant of each gene differed from that in wild-type cells. These results suggest that Os1348 is involved in antibiotic activity and that the structure or expression of this protein is under the control of downstream gene products.